Prototype of Automatic Waste Filter with Load Sensor Cell on Drainage Waters - Nurlisa, Siti; Nasution, Mulkan Iskandar; Nasution, Nazaruddin (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February EditionDO - 10.24843/BF.2024.V25.i01.p18, 2024)
Waste is a classic problem for developing countries like Indonesia. Human awareness regarding waste is still minimal, which is also a cause for concern, this has an impact on the increase in waste produced every year. Regarding the large amount of rubbish that humans throw away carelessly, it sometimes has very bad consequences for the environment. One of them is the blockage of rubbish in the drainage channel. The aim of this research is to find out the design and deviation value of the design of the automatic rubbish filter system at the drainage gate using a load cell sensor. The working system of the automatic rubbish filter is a rotating rubbish filter using 10 rpm DC gearbox motor, then the waste that has been successfully filtered is dropped through a conveyor to be taken to the trash bin and the value of the waste load that has been successfully filtered is calculated using a load cell sensor and displayed on the Liquid Cristal Display (LCD) screen. From the input and output test results states that the load cell sensor has a low error rate, namely 0.01%, with a waste weight reading on the load cell sensor, namely 316 g, and the highest error rate, namely 0.06%, with a waste weight reading on the load cell sensor, namely 109 g.